An Exploration of the Effect of Hemodynamic Changes Due to Normal Aging on the fNIRS Response to Semantic Processing of Words - Amiri, Mahnoush; Pouliot, Philippe; Bonnéry, Clément; Leclerc, Paul-Olivier; Desjardins, Michèle; Lesage, Frédéric; Joanette, Yves (Frontiers in Neurology, 2014)
Like other neuroimaging techniques assessing cerebral blood oxygenation, near-infrared spectroscopy (NIRS) has been applied in many neurocognitive studies. With NIRS, neural activation can be explored indirectly via hemodynamic changes in the imaged region. In studies of aging, changes in baseline physiology and brain anatomy confound NIRS measures seeking to investigate age-related changes in neuronal activity. The field is thus hampered by the complexity of the aging process itself, and statistical inferences from functional data acquired by optical imaging techniques must be interpreted with care. Multimodal integration of NIRS with both structural and baseline physiological assessments is crucial to avoid misinterpreting neuroimaging signals. In this study, a combination of two different optical techniques, anatomical MRI and Arterial Spin Labeling (ASL) was used to investigate age-related changes in activation during a lexical-semantic processing task. Quantitative analysis revealed decreased baseline oxyhemoglobin and cerebral blood flow in the older adults. Using baseline physiology measures as regressors in the investigation of functional concentration changes when doing analyses of variance, we found significant changes in task-induced areas of activity. In the right hemisphere, more significant age-related activity was observed around the junction of the inferior frontal gyrus and inferior precentral sulcus, along with engagement of Wernicke’s area. In the left hemisphere, the degree and extent of frontal activation, including the dorsolateral prefrontal cortex and inferior frontal gyrus, differed between age groups. Measuring background physiological differences and using their values as regressors in statistical analyses allowed a more appropriate, age-corrected understanding of the functional differentiations between age groups. Age-corrected baselines are thus essential to investigate which components of the NIRS signal are altered by aging.